Arabidopsis Pollen Fertility Requires the Transcription Factors CITF1 and SPL7 That Regulate Copper Delivery to Anthers and Jasmonic Acid Synthesis. Issue 12 (17th November 2017) - Yan, Jiapei; Chia, Ju-Chen; Sheng, Huajin; Jung, Ha-il; Zavodna, Tetiana-Olena; Zhang, Lu; Huang, Rong; Jiao, Chen; Craft, Eric J.; Fei, Zhangjun; Kochian, Leon V.; Vatamaniuk, Olena K.
Abstract : Transcription factors CITF1 and SPL7 regulate the delivery of a micronutrient copper to anthers, thereby influencing fertility, and link copper homeostasis and the jasmonic acid metabolic pathway. Abstract: A deficiency of the micronutrient copper (Cu) leads to infertility and grain/seed yield reduction in plants. How Cu affects fertility, which reproductive structures require Cu, and which transcriptional networks coordinate Cu delivery to reproductive organs is poorly understood. Using RNA-seq analysis, we showed that the expression of a gene encoding a novel transcription factor, CITF1 (Cu-DEFICIENCY INDUCED TRANSCRIPTION FACTOR1), was strongly upregulated in Arabidopsis thaliana flowers subjected to Cu deficiency. We demonstrated that CITF1 regulates Cu uptake into roots and delivery to flowers and is required for normal plant growth under Cu deficiency. CITF1 acts together with a master regulator of copper homeostasis, SPL7 (SQUAMOSA PROMOTER BINDING PROTEIN LIKE7), and the function of both is required for Cu delivery to anthers and pollen fertility. We also found that Cu deficiency upregulates the expression of jasmonic acid (JA) biosynthetic genes in flowers and increases endogenous JA accumulation in leaves. These effects are controlled in part by CITF1 and SPL7. Finally, we show that JA regulates CITF1 expression and that the JA biosynthetic mutant lacking the CITF1- and SPL7-regulated genes, LOX3 and LOX4, is sensitive to Cu deficiency. Together, our data show that CITF1 and SPL7 regulate Cu uptake and delivery to anthers, thereby influencing fertility, and highlight the relationship between Cu homeostasis, CITF1, SPL7, and the JA metabolic pathway.